The Impact of Work Family Interferences on Work Life Conflict among the Workers of Kcmmf (Milma) In Kerala - Ramesh.V.M, AND R. Sakthivel (Journal of Research in Humanities and Social Science, 2015)
The definition of work conflict is a form of interface of work and family demands in which the role pressures from the work domain. It is important for any organization to know about the factors that cause the work conflict of employees, which may be related to both work and personal profile. This implies a bi- directional relationship where work can interfere with non-work responsibilities (work life conflict) and vice versa (life work conflict). It is important for any organization to know about how the workers are balancing the work and family conflict, which may be related to both work and personal profile. It is also the responsibility of the organization to evaluate these factors and provide support to the employees to balance between work life and family life. The study was conducted with the help of the structured questionnaire which was administered among the sample of 411 respondents in the MILMA units in Kerala. The data collected have been organized, classified and analyzed using a wide range of appropriate statistical tools.